The Velocities of Ion Transport Into and Through the Xylem of Roots: Findings with a Two-Point Application Pulse-Chase Technique - Epstein, Emanuel (1973)
Excised corn roots, Zea mays, had radioactively labeled solution applied at two points along their length, for 1 minute, and were then kept in dilute, unlabeled nutrient solution. During this “chase” period, exudate was collected at 1-minute intervals, and its content of radioions was determined. Two pulses of label appeared in succession, originating at the points of application near the cut end of the root and farther from the cut end, respectively. Calculation yields the velocity at which the ions moved radially across the root into the xylem (v(r)) and the velocity at which they moved longitudinally within the xylem (v(l)). For Rb(+) labeled with (86)Rb, v(r) was 1.8 and v(l), 35 cm/hr. For Br(−) labeled with (82)Br, v(r) was 1.4 and v(l), 103 cm/hr.